Actualización en psicodermatología - Serón D., Tomás; Calderón H., Perla (Revista Hospital Clínico Universidad de Chile, 2015)
Psychodermatology is an area of dermatology dedicated to the connection between this medical discipline and psychiatry. Its importance is based in that emotional factors can exacerbate skin diseases and psychiatric disorders may manifest as skin lesions. This relationship can be described as an intricate network involving psychological, social, neuroendocrine, immune and skin factors, as reflected in the complexity of the management of these patients. Is important to increase research and interest in this important issue, as an integrative and multidisciplinary approach allows for interventions in the vicious circle between psychiatric dysfunction and skin symptoms, improving significantly the quality of life of patients.